Incentivo dos componentes psicossociais na trajetória de atletas de voleibol - Mendes, Matheus Santos; Mendes, Felipe Goedert; Milistetd, Michel; Collet, Carine; Vieira do Nascimento, Juarez (2017)
Aim: To compare the support of the psychosocial components in different phases of sporting trajectory in volleyball underage teams. Methods: A specific questionnaire based on the Developmental Model Sport Participation (Côté, 1999; Côté et al., 2016) was applied to 78 male athletes with an average age of 19.24 ± 0.9 years old from Brazilian national outstanding clubs. The chi-square test and the multinomial logistic regression were used to compare the level of support of the psychosocial components for the practice of volleyball and other sports in each phase of the sporting trajectory, adopting a significance level of 5%. Results: The psychosocial components encourage not only the practice of the target sport, but also the practice of other sports. However, the encouragement of family members (p≤0.001), friends (p≤0.001) and coaches (p≤0.001) for the practice of volleyball increased during the course of the sport, the support to practice other sports remained stable. Conclusion: The psychosocial components play an important role in the sporting trajectory of volleyball athletes in Brazilian national outstanding clubs. By adding reflections on the importance of psychosocial components in an individual's sporting life, the findings provide clues to federations, clubs, and sports associations for structuring sport training programs in the sport.
Objetivo: Comparar o incentivo dos componentes psicossociais nas diferentes fases da trajetória esportiva em atletas de voleibol nas categorias de formaçao. Métodos: Aplicou-se um questionário específico baseado nos elementos dinâmicos da formaçao esportiva (Côté, 1999; Côté, Turnnidge, & Vierimaa, 2016) em 78 atletas do sexo masculino com média de idade de 19.24 ± 0.9 anos de clubes de reconhecimento nacional brasileiro. Utilizou-se o teste qui-quadrado e a regressao logística multinomial para comparar o nível de incentivo dos componentes psicossociais à prática de voleibol e de outras modalidades em cada fase da trajetória esportiva, adotando nível de significância de 5%. Resultados: Os componentes psicossociais incentivam nao apenas à prática da modalidade alvo, mas também à prática de outras modalidades. Entretanto, o incentivo dos familiares (p≤;0,001), amigos (p≤0,001) e treinadores (p≤0,001) à prática do voleibol aumentou no decorrer da trajetória esportiva, permanecendo estável o incentivo à prática das demais modalidades esportivas. Conclusao: Os componentes psicossociais exercem importante papel na trajetória esportiva de atletas de voleibol em clubes de reconhecimento nacional brasileiro. Ao agregarem reflexoes sobre a importância dos componentes psicossociais na vida esportiva de um indivíduo, os achados fornecem pistas às federaçoes, clubes e locais de iniciaçao esportiva para estruturaçao de programas de formaçao esportiva na modalidade
Keywords: Sporting formation; Volleyball; Sporting trajectory; Phychosocial components; Formaçao esportiva^lpt; Voleibol; Trajetória esportiva; Componentes psicossociais; Juegos de pelota; Trayectoria del estudiante